Microalgae enhance cadmium accumulation in Perilla frutescens: root structural adaptation and secretion-mediated detoxification - Ren, Ying; Su, Yuying; Li, Jinfeng; Zhang, Hui; Yang, Yumeng; Li, Yuanyuan; Chen, Juan; Pang, Xiaohui; Zhang, Zheng; Han, Jianping (Frontiers in Plant Science, 2025)
IntroductionCadmium (Cd) phytoremediation is often constrained by the low accumulation capacity and limited stress tolerance of most plant species. Developing approaches to overcome these limitations is essential for more efficient phytoremediation.MethodsThe effect of microalgae supplementation on Cd phytoextraction in Perilla frutescens was evaluated under Cd stress, with plant growth, Cd accumulation, and root physiological, structural, and metabolic responses examined to elucidate the underlying mechanisms.ResultsMicroalgae supplementation significantly enhanced total plant biomass by 37.43% while increasing Cd accumulation by 20.72% in roots, 25.87% in stems, and 112.29% in leaves relative to Cd-only treatment. These improvements were closely associated with microalgae-induced physiological adaptations in roots, characterized by elevated peroxidase activity, reduced superoxide anion generation, and mitigated lipid peroxidation. Microalgae treatment also promoted Cd retention in root cell walls, with hemicellulose I showing a 166.37% increase in Cd binding (p < 0.05). Ultrastructural and spectroscopic analyses indicated that this enhancement likely stems from optimized root cell wall structure and increased functional group activity. Additionally, microalgae dramatically altered root exudate composition, increasing secretion of metal-chelating and antioxidant compounds such as ferulic acid, artemisinic acid, and dihydroartemisinin, whose concentrations were positively correlated with plant Cd accumulation.DiscussionThese findings indicate that microalgae enhanced Cd phytoextraction in Perilla frutescens through modulation of root structural and metabolic traits, leading to enhanced Cd accumulation and tolerance. Microalgae-assisted phytoremediation may thus provide a viable strategy for remediating Cd-contaminated environments.